Developing a parental empowerment model to prevent health risk behaviors among adolescents in East Java, Indonesia - Krisnana, Dr. Ilya; Rachmawati, Praba Diyan; Kurnia, Iqlima Dwi; Wahyuni, Lutfi; Rithpo, Pratuma (Universitas Airlangga, 2024)
Introduction: Parental empowerment in monitoring adolescents plays a crucial role in preventing health-risk behaviors. This research aimed to develop a model of parental empowerment against the prevention of health risk behavior (PE-HRB) in adolescents based on the theory of health promotion model. Methods: The research design used was an explanative survey method. The research population was parents who have adolescent children in East Java and able to access online questionnaires. Consecutive sampling obtained a large sample of 704 respondents from July - September 2020. Questionnaires were distributed online using the online Zoho platform and distributed to parents. The data analysis used a smart PLS (Partial Least Squares) statistical test with significance level T>1.96. Results: Personal factors positively and significantly influenced cognition and affect (T=2.82;p=0.005). Cognition and affection variables influence on parental empowerment (T=5.19; p=<.001). Cognition and affection have no effect on preventive behavior (T=1.49; p=.135). Parental empowerment is an important point in shaping preventive behavior. Conclusions: Empowerment is a factor that significantly affects the formation of parental behavior without going through commitment variables. Parental involvement in adolescents' academic and personal lives is an important aspect to prevent health-risk behavior in adolescents. Cognition and affection variables cannot directly form preventive behavior but must go through parental empowerment pathways to form preventive behavior. Parental empowerment has no effect on commitment, but commitment affects prevention behavior. Empowering parents is a topic that can be used as material in health education in primary health services.